South Asia in transition conflicts and tensions - Bahadur, Kalim 1936-.; Indian Centre for Regional Affairs (New Delhi Patriot Publishers, 1986)
Papers presented at a seminar organized by the Indian Centre for Regional Affairs, 1985.
Keywords: South Asia -- Politics and government; South Asia -- Social conditions